GERMINATION OF EUCALYPTUS SEEDS UNDER WATER AND SALT STRESS - Martins, Cibele Chalita [UNESP] (2014)
The knowledge of the physiology of Eucalyptus spp. germination may contribute significantly to the development of management and choice of suitability of the deployment areas. The aim was to evaluate the effects of water and salt stress on seed germination of Eucalyptus camaldulensis, E. citriodora, E. grandis, E. robusta and E. urophylla. The seeding was done with four replicates of 0.05 g of seeds in paper moistened with solutions at potentials of 0.0, -0.2, -0.4, and -0.8 MPa, induced with polyethylene glycol (PEG 6000) and NaCl. The germination test was in 25 degrees C in the presence of light. Were evaluated the first test score seven days after sowing, and weekly germination (normal seedlings) until 28 days. Were also calculated the germination speed index. Water stress causes a greater reduction in the rate of germination and accumulated germination of E. camaldulensis and E. citriodora seeds than salt stress, and the seeds of E. robusta are more adapted to germinate under salt stress moderate, between -0.2 and -0.4 MPa. Regardless of the substance used to induce stress, the threshold for germination was -0.8 MPa. The E. camaldulensis is the most sensitive specie to water stress and E. urophylla most sensitive to salt stress.